ANALISIS MOTIVASI PETUGAS KESEHATAN TERHADAP PENANGGULANGAN COVID-19 DI PUSKESMAS JAKABARING : Dewi Sayati (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
A study on work motivation needs to be carried out because during the Covid-19 pandemic it takes work encouragement from health workers so that they can work optimally so that the role of puskesmas during the Covid-19 pandemic can be optimal. The high transmission power of this disease causes health workers, especially in health centers to be vulnerable to this disease. The purpose of this study was to find out the analysis of the work motivation of health workers against Covid-19 at the Jakabaring Health Center, Banyuasin Regency. The method in this research is this research is quantitative research and the approach used in this research is descriptive analytical approach, on the grounds that this research uses numbers or calculations in data collection and provides an overview of the object under study through sample or population data as existence. The research design used Cross Sectional. The results showed that working conditions (p=0.001), interpersonal relationships (p=0.004) and the responsibility of health workers (p=0.007). ada hubungan antara kondisi kerja, hubungan interpersonal, dan tanggung jawab terhadap penanggulangan covid-19. It is recommended that the Puskesmas which is the front line, is expected to be able to maintain and create working conditions and interpersonal relationships between subordinates and superiors by means of regular meetings, such as scientific meetings. So that effective communication can be established in solving patient health problems